Neuroprotective effects of seaweeds against 6-hydroxidopamine-induced cell death on an in vitro human neuroblastoma model - Silva, Joana (2020)
Background: Parkinson’s disease (PD) is a progressive neurodegenerative disorder of the central nervous system. Although the causes of PD pathogenesis remain incomplete, some evidences has suggested that oxidative stress is an important mediator in its pathogenesis. The aim of this study was to evaluate the protective effects of seaweeds with high antioxidant activity on 6-hydroxydopamine (6-OHDA)-induced neurotoxicity in the human neuroblastoma cell line SH-SY5Y, as well as the associated intracellular signaling pathways. Methods: Cell viability studies were assessed by 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium (MTT) bromide assay and the intracellular signaling pathways analyzed were: hydrogen peroxide (H2O2) production, changes in the mitochondrial membrane potential and Caspase-3 activity. Results: Exposure of SH-SY5Y cells to 6-OHDA (10–1000 μM) reduced cell’s viability in a concentration and timedependent manner. The data suggest that the cell death induced by 6-OHDA was mediated by an increase of H2O2 production, the depolarization of mitochondrial membrane potential and the increase of Caspase-3 activity. Extracts from S. polyshides, P. pavonica, S. muticum, C. tomentosum and U. compressa revealed to efficiently protect cell’s viability in the presence of 6-OHDA (100 μM; 24 h). These effects appear to be associated with the reduction of H2O2 cell’s production, the protection of mitochondrial membrane’s potential and the reduction of Caspase-3 activity. Conclusions: These results suggest that seaweeds can be a promising source of new compounds with neuroprotective potential.